Development and characterization of allicin using palm stearin as a binder on urea granules. (15th March 2020) - Affendi, Nur Mahfuzah Noor; Mansor, Nurlidia; Mathialagan, Ranitha
Abstract: The potency of allicin as a urease inhibitor has been discovered and the demand for using a biodegradable material as a coating is increasing. The loss of nitrogen can be reduced, and the efficiency of the fertilizer can be increased by utilizing a coating. The objective of this study was to determine the compatibility of allicin and urea with palm stearin as an adhesive agent in the coating process. Four treatments were used in this study; urea as the control, urea coated with palm stearin (UPS), urea coated with allicin and palm stearin (UPSA) and urea coated with NBPT (UNBPT). The treatments were analyzed for thickness, chemical structure, total N content, dissolution rate in water and hardness. Results from FT-IR and SEM images demonstrated that palm stearin was compatible with allicin and urea with smoother coated layer. The efficiency of coated urea with allicin and plam stearin was enhanced by reducing 70% of urea release in 24 hours as compared to the urea. The crushing strength was significantly improved by using palm stearin as the binder. Coating urea with palm stearin and allicin appears to increase the efficiency of urea.